Kemandegan CSR dan Kontribusinya terhadap Perluasan Konflik Agraria di Kawasan Hutan Register 45 Mesuji - Pujiriyani, Dwi Wulan; Wahab, Oki Hajiansyah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2013)
This paper seeks to examine Corporate Social Responsibility (CSR) in its relations to agrarian conflict that occurred in the Register 45, Mesuji, Lampung. The Joint Fact Finding Team (TGPF) revealed that in 2012, one of the causes for conflict that occurred between PT Silva Inhutani and the community was because the company did not carry out CSR program. This research was conducted through field research with interview and observation as its two main techniques. The result of this research shows that CSR was not implemented seriously. CSR tends to be only a dream instead of an ideal fact. In its relations to agrarian conflict in Mesuji, it was proven that CSR program that executed by the company was unable to contribute to the process of conflict resolution between the company and the society. Although the company has started to carry out CSR program, it did not have much meaning because it was a short term program with a characteristic of charity.